GUIDANCE AND COUNSELLING IN HEARING IMPAIRMENT STUDENTS INTEGRATION PROGRAM (Proceedings of International Conference on Special Education, 2015)
This study aims to identify the implementation of guidance and counselling services for the hearing impaired students in the special education program integration (PPKI) hearing impaired in the secondary school. The qualitative case study method was used to obtain data on these aspects. The data was collected by using the interview techniques and all the data were analyzed with the aid of N'Vivo8. The participants consisted of six guidance and counselling teachers, six special education teachers and three hearing impaired students. The study found out that the implementation of guidance and counselling services is still a lack in PPKI hearing impaired. The guidance and counselling teachers were just only doing some individual counselling while group guidance were more frequently performed. The guidance and counselling teachers are still vague in performing these services because they have no clear guidelines from the Ministry of Education. The conclusions of this study have implications in terms of the practice in guidance and counselling in PPKI hearing impaired, the preparation of the guidance and counselling teachers, the Minstry of Education, and needs further study in this field. Guidance and counselling services in schools now need to engage pupils with special educational. Teacher guidance and counselling should be given courses on how to handle special education students.